High Cost and Low Trust: Insights From Qualitative Commercial Fishing Cost Data in the Northeast United States - Elizabeth D. Conley; Samantha Werner; Gregory Ardini; Matthew Cutler; Patricia M. Clay (Fisheries Management and Ecology, 2026)
In fisheries management, socioeconomic data, specifically qualitative data analysis, is often underutilized. This study qualitatively analyzed a primary federal data collection effort in the Northeast United States, The Greater Atlantic Region Commercial Fishing Business Cost Survey. This analysis focused on how commercial harvester perceptions of business costs and the industry evolved during 2006–2022. The results show that harvesters initially described perceptions of not generating enough profit to sustain a livelihood, as well as feelings of industry uncertainty, mismanagement, and dissatisfaction. These perceptions became drivers of increased harvester distrust of managers and management processes. This research demonstrates the need for incorporating harvester perceptions in future policy analyses to understand and reduce financial and systemic burdens. Use of harvester perceptions illuminates areas of concern that need to be addressed to strengthen relationships while simultaneously encouraging knowledge co‐production, co‐management, and increasing sustainability of fishery resources. Here, we exemplify the importance of utilizing qualitative data to provide valuable insights such as a deeper understanding of social dynamics and stakeholder perspectives and go on to explore the root causes and evolution of distrust between harvesters and managers. This study offers applications to better assess, address, mitigate, and rebuild trust to meet complex resource management goals.

Impacts of rotation, tillage, cover cropping, and drainage on soil health in soybean-based cropping systems: Evidence from 4–50-year trials across the US - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Chad D. Lee; David Jordan; Hanna J. Poffenbarger; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Agriculture, Ecosystems & Environment, 2026)

Soybean yield response to management practices (4–40 years) and soil health parameters - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Spyridon Mourtzinis; Chad D. Lee; David Jordan; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Field Crops Research, 2025)

Performance and energy costs associated with scaling infrared heater arrays for warming field plots from 1 to 100 m - Bruce A. Kimball; Matthew M. Conley; Keith F. Lewin (Theoretical and Applied Climatology, 2012)

Infrared heater arrays for warming ecosystem field plots - BRUCE A. KIMBALL; MATTHEW M. CONLEY; SHIPING WANG; XINGWU LIN; CAIYUN LUO; JACK MORGAN; DAVID SMITH (Global Change Biology, 2008)
There is a need for methodology to warm open‐field plots in order to study the likely effects of global warming on ecosystems in the future. Herein, we describe the development of arrays of more powerful and efficient infrared heaters with ceramic heating elements. By tilting the heaters at 45° from horizontal and combining six of them in a hexagonal array, good uniformity of warming was achieved across 3‐m‐diameter plots. Moreover, there do not appear to be obstacles (other than financial) to scaling to larger plots. The efficiency [ η h (%); thermal radiation out per electrical energy in] of these heaters was higher than that of the heaters used in most previous infrared heater experiments and can be described by: η h = 10 + 25exp(− 0.17 u ), where u is wind speed at 2 m height (m s − 1 ). Graphs are presented to estimate operating costs from degrees of warming, two types of plant canopy, and site windiness. Four such arrays were deployed over plots of grass at Haibei, Qinghai, China and another at Cheyenne, Wyoming, USA, along with corresponding reference plots with dummy heaters. Proportional integral derivative systems with infrared thermometers to sense canopy temperatures of the heated and reference plots were used to control the heater outputs. Over month‐long periods at both sites, about 75% of canopy temperature observations were within 0.5 °C of the set‐point temperature differences between heated and reference plots. Electrical power consumption per 3‐m‐diameter plot averaged 58 and 80 kW h day − 1 for Haibei and Cheyenne, respectively. However, the desired temperature differences were set lower at Haibei (1.2 °C daytime, 1.7 °C night) than Cheyenne (1.5 °C daytime, 3.0 °C night), and Cheyenne is a windier site. Thus, we conclude that these hexagonal arrays of ceramic infrared heaters can be a successful temperature free‐air‐controlled enhancement (T‐FACE) system for warming ecosystem field plots.